The Unfinished Project of Roncarelli v. Duplessis: Justiciability, Discretion, and the Limits of the Rule of Law - Sossin, Lorne (McGill Law Journal, 2010)
Roncarelli is remembered fifty years later particularly because of Justice Rand’s now iconic statement that “there is no such thing as absolute and untrammelled discretion.” Justice Rand defined “untrammelled discretion” as circumstances where action can be taken on any ground or for any reason that can be suggested to the mind of the decision maker. This statement has been understood to mean that all public regulation exercised through discretionary decision-making by executive officials has legal boundaries, and that the role of the courts is to ensure that decisions do not exceed those boundaries.